Asset bubbles and product market competition - Francisco Queirós (Theoretical Economics, 2024)
This paper studies the interplay between asset bubbles and product market competition. It offers two main insights. The first is that imperfect competition creates a wedge between interest rates and the marginal product of capital. This makes rational bubbles possible even when there is no overaccumulation of capital. The second is that, when providing a production subsidy, bubbles stimulate competition and reduce monopoly rents. I show that bubbles can destroy efficient investment and have ambiguous welfare consequences. However, when they stimulate competition, they can have crowding-in effects on capital.
Keywords: E44; L13; L16; 330; competition; market power; overaccumulation; Rational bubbles